Pengaruh Sosial Media Marketing terhadap Keputusan Pembelian Konsumen di Marketplace Tokopedia (Studi Kasus: Mahasiswa Politeknik Negeri Bandung) - Regina Manuella (Asosiasi Ahli Administrasi Indonesia, 2023)
The purpose of this study was to determine the effect of social media marketing on purchasing decisions on the Tokopedia marketplace. Researchers conducted an analysis of 110 Bandung State Polytechnic student respondents who actively use social media through the distribution of google form questionnaires. Researchers used descriptive analysis, validity test, reliability test, normality test, simple regression analysis, and coefficients to determine the effect value of the independent variables and the dependent variable. The results showed 27.8% of marketing through social media, this shows a sufficient percentage to influence the purchasing decisions of Bandung State Polytechnic students to shop at the Tokopedia marketplace.